2023
DOI: 10.1177/0271678x231159597
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BACE1-mediated production of amyloid beta improves hippocampal synaptic function in an experimental model of ischemic stroke

Abstract: Post-stroke cognitive impairment and dementia (PSCID) affects many survivors of large vessel cerebral ischemia. The molecular pathways underlying PSCID are poorly defined but may overlap with neurodegenerative pathophysiology. Specifically, synaptic dysfunction after stroke may be directly mediated by alterations in the levels of amyloid beta (Aβ), the peptide that accumulates in the brains of Alzheimer’s disease (AD) patients. In this study, we use the transient middle cerebral artery occlusion (MCAo) model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…BACE1 is a crucial enzyme in Aβ synthesis, and its mRNA and protein levels increase after ischemic stroke [62]. To investigate the effects of hypoxia on the BACE1 promoter, we used a reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…BACE1 is a crucial enzyme in Aβ synthesis, and its mRNA and protein levels increase after ischemic stroke [62]. To investigate the effects of hypoxia on the BACE1 promoter, we used a reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…12,106,107 While it is well-known that there are many theories about AD pathogenesis, the deposition of senile plaques plays a very important role, which is why scientists have since long focused more on Aβ to identify effective therapeutic agents. 114,115 Fortunately, aducanumab has been approved for clinical use in the treatment of AD. As an alternative treatment of AD, traditional…”
Section: Ols Also Participate In Other Ad Pathologiesmentioning
confidence: 99%
“…In addition, Enterobacteriaceae , one of the microorganisms, metabolizes lipopolysaccharide, which not only leads to the release of pro-inflammatory factors, but also leads to the deposition of β-amyloid ( Płóciennikowska et al, 2015 ). Most animal studies have shown that β-amyloid is often deposited in the thalamus after stroke ( van Groen et al, 2005 ; Mäkinen et al, 2008 ; Zhang J. et al, 2012 ), while other studies have found that β-amyloid is deposited in the hippocampus ( Dietrich et al, 1998 ; Basak et al, 2023 ). It is well known that the thalamic nuclei play an important role in cognitive function ( Dalrymple-Alford et al, 2015 ), and the hippocampus is closely related to the thalamic nuclei ( Braak et al, 1996 ).…”
Section: The Clinical Application Prospect Of Multi-omics In Pscimentioning
confidence: 99%